Examining Purchase Intention Toward Packaged Red Fruit Herbal Products: The Role Of Green Perceived Quality, Word Of Mouth, And Health Consciousness - Rudolf Anthonius; Sri Astuti Pratminingsih (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Kuningan, 2026)
This study examines the marketing of packaged red fruit (Pandanus conoideus) as a green product, specifically analyzing whether Green Perceived Quality, Word of Mouth, and Health Consciousness have a positive effect on Purchase Intention for packaged red fruit herbal products in West Manokwari District, Manokwari Regency, West Papua. The local wisdom embedded in this product, as a distinctive herbal flagship of Papua, makes it an interesting subject of study due to its substantial health benefits, including antioxidant content, beta-carotene, and its role in supporting the immune system and preventing degenerative diseases. Given the high production value of red fruit, it should be optimally utilized by the community in a more practical packaged form. Therefore, this study employed a quantitative research approach using a sample of 135 respondents, with the unit of analysis being the community in West Manokwari District, Manokwari Regency, West Papua. The data were analyzed using multiple linear regression. The results of hypothesis testing indicate that Word of Mouth and Health Consciousness have positive effects on Purchase Intention for packaged red-fruit herbal products in West Manokwari District, Manokwari Regency, West Papua, whereas Green Perceived Quality does not. Thus, two hypotheses are accepted, whereas one hypothesis is rejected.